Evaluation of Retention and Fracture Strength of All Ceramic Crowns with Three Different Esthetic Cast Post–Core Systems - Sina Safari; Amirmohammad Mirzapour; Roya Sadrmohammadi (International Journal of Dentistry)
Purpose. This study investigates the fracture and retention strength of all-ceramic crowns with modified composite resin and ceramic cores compared to conventional casted post and core systems. Materials and Methods. A prepared human central tooth was initially scanned to design and 3D print the post and core. Subsequently, 40 bovine teeth were adjusted to accommodate the fabricated post and cores. They were then divided into four groups of 10 each: group 1 comprised cast cores without cover (control group), group 2 involved cast cores reduced and replaced with IPS Empress material (IPS group), group 3 consisted of cast cores covered with opaque composite (composite group), and group 4 included cast cores covered with opaque ceramic (ceramic group). Zirconia crowns were cemented onto all samples. After an aging process, pull-off and fracture strength tests were conducted. Fracture strength was determined by applying a compressive force at an angle of 135° to the tooth’s longitudinal axis until the fracture occurred. For retention strength assessment, a universal testing machine with a 10 mm/min crosshead speed was employed. The resulting data underwent statistical analysis utilizing two-way analysis of variance (ANOVA) and Mann–Whitney U tests. Results. The analysis revealed no significant difference in fracture strength among the groups (P-value = 0.997). However, the retention strength of the control and IPS groups was significantly higher than that of the other groups. Conclusion. There were no discernible distinctions among the three study methods regarding fracture strength. Nonetheless, the retention strength of the IPS group resembled that of the control group, surpassing that of the composite and ceramic groups.